Interactions 1 : Writing - Pavlik, Cheryl (Tổng hợp Thành phố Hồ Chí Minh, 2009)
Mosaic Silver Edition is a fully integrated academic skills series that combines the best of print with the convenience of digital delivery. Language proficiencies are articulated from the beginning through advanced levels within each of the four language-skill strands. Chapter themes articulate across the four strands to systematically recycle content, vocabulary and grammar.